The first integral method for wu-zhang nonlinear system with time-dependent coefficients - Baleanu, Dumitru; Kilic, Bulent; İnç, Mustafa (Editura Academiei Romane, 2015)
The first integral method is used to construct traveling wave solutions of Wu-Zhang nonlinear dynamical system with time-dependent coefficients. We obtained different types of exact solutions by using two types of variable transformations. The method is an effective tool to construct the different types of exact solutions of nonlinear partial differential equations having real world applications.
Keywords: Analytical solutions; First integral method; Traveling wave solutions.; Wu-Zhang system